New documented records for the Black-collared Hawk (Busarellus nigricollis, Latham 1790) (Aves: Accipitridae) in Rio Grande do Sul state - Dante Andres Meller; Roberta Porto Rödel; Carlos Eduardo Agne (Acta Biológica Catarinense, 2023)
The Black-collared Hawk (Busarellus nigricollis) is a buteonine with a wide distribution through neotropical region. It has preference for aquatic habitats, where it feeds on fishes. It has few records for southern Brazil. In Rio Grande do Sul (RS) State, it is rare, and the only documented record is a collected specimen in Santa Cruz do Sul, more than seventy years ago. Here we report new documented records for western and central region of RS. The first one was a juvenile observed in December 2020 at the Wetland of Butuí-mirim. The second one was an immature observed on April 2021 at Butuí River. Both observations were made in São Borja, and reaffirm its occurrence in the Butuí River Basin. The third record was in the central region of RS in June 2022, and its occurrence may be associated to the low Jacuí River. The regional status of the Black-collared Hawk is unclear. It was considered threatened in the past, but now it is regarded as not applicable for evaluation. The Butuí River Basin has many wetlands in the course of its rivers, although some were drained and converted into rice fields. Future actions should be considered regarding the conservation of the wetlands of Butuí River Basin.